2013
DOI: 10.1177/2047487313488300
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intensive glycaemic control on endothelial progenitor cells in patients with long-standing uncontrolled type 2 diabetes

Abstract: In patients with uncontrolled long-standing type 2 diabetes, intensive glycaemic control was associated with an increase in the levels of circulating EPCs, and improvement in their functional properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
1
15
0
1
Order By: Relevance
“…The correlation between changes in levels of EPCs and corresponding changes in the CIMT was assessed using Spearman's coefficients of correlation. Participants were divided into groups of low (scores of 0-3), middle (4-5) and high (6)(7)(8)(9) adherence to the Mediterranean diet based on their diet scores for analysis. Comparisons were conducted using linear regression to test for trends across the Mediterranean dietary pattern score groups for EPCs and CIMT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between changes in levels of EPCs and corresponding changes in the CIMT was assessed using Spearman's coefficients of correlation. Participants were divided into groups of low (scores of 0-3), middle (4-5) and high (6)(7)(8)(9) adherence to the Mediterranean diet based on their diet scores for analysis. Comparisons were conducted using linear regression to test for trends across the Mediterranean dietary pattern score groups for EPCs and CIMT.…”
Section: Discussionmentioning
confidence: 99%
“…6 A reduction in EPCs may represent one of the mechanisms linking increased vascular risk with diabetes mellitus. 7 The effect of a Mediterranean diet on circulating EPCs has never been investigated in patients with type 2 diabetes free of cardiovascular disease (CVD). Therefore, using the data from a randomized trial (MÈ DITA; MEditerranean DIet and Type 2 diAbetes), 8 we investigated (a) whether a Mediterranean diet affected circulating levels of EPCs in patients newly diagnosed with type 2 diabetes, (b) whether changes in circulating levels of EPCs were associated with changes in the carotid intima-media thickness (CIMT), considered to be a surrogate marker for CVD in patients with type 2 diabetes 9 and (c) whether the effect was sustained during long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies displayed reduced levels of circulating EPCs with attenuated functional properties in patients with diabetes mellitus when compared to non-diabetics, and found that tight glycemic control improved their functional capabilities [12]. However, it is not known by which mechanisms diabetes mellitus affects these cells.…”
Section: Discussionmentioning
confidence: 99%
“…The circulating endothelial progenitor cells count has also been proposed as a surrogate marker of vascular dysfunction and is reduced in patients with various CV risk factors [3]. Furthermore, diabetes mellitus is known to have a deleterious effect on EPC function and level, and tight glycemic control was associated with an increase in EPCs levels and improvement in their functional properties [12]. …”
Section: Introductionmentioning
confidence: 99%
“…В исследовании Churdchomjan W. с соавт. продемонстрировано сниже-ние количества циркулирующих ЭПК у больных СД2 с неудовлетворительным контролем гликемии (уровень HbA 1c >7,0%) по сравнению с пациентами с удовлетвори-тельным контролем гликемии (уровень HbA 1c ≤7,0%) [24]. В двух последующих работах исследователи наблюдали динамику ЭПК в зависимости от интенсивности глике-мического контроля у больных СД2.…”
Section: сахарный диабет Diabetes Mellitusunclassified